Simulation and economic study of hydrogen production from biomass and RDF gasification. Issue 12 (2nd December 2017) - Wang, Gui-Rong; Li, De-Xun; Ruan, Wen-Biao; Jin, Chen-Lin
ABSTRACT: Biomass is a renewable source of energy, which refers to plant-based organic materials such as agricultural residue, woody biomass, and algal biomass, which can be directly used as a feedstock for energy systems gas engines, and gas turbines or as a fuel for the production of other light fuels such as hydrogen gas. In this paper, an equilibrium model of gasification process was developed to study the economic properties of biomass gasification such as hydrogen production cost (HPC) and fixed capital investment (FCI). When the plant size increased from 1500 to 2500 (dry metric tonne per day), HPC decreased from 3.2 to 2.4 €/kg for agricultural residue, from 3.45 to 2.5 €/kg for green algae, and from 4.4 to 3.85 €/kg for RDF. Simulated results also showed as the stoichiometric ratio increases from 0.23 to 0.45, concentrations of H2, CO, and CH4 decrease, while CO2 increases because of the thermal cracking of heavier hydrocarbons and char combustion at higher stoichiometric ratios.